2012
DOI: 10.1097/prs.0b013e31826d104f
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Endogenous and Exogenous Factors to Female Alopecia

Abstract: This study implicates several environmental risk factors in the pathophysiology of female alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…One limitation of this study is that AGA may be affected by many genes that have not yet been identified; twin studies have shown that the AGA condition is heritable, and a family history of AGA has been included in our analysis for this reason. However, there are still many findings [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88] that suggest that heritable and epigenetic [69], [89] differences also play a role in alopecia; this may replace the classical discussion of the roles of genetic and environmental factors in alopecia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of this study is that AGA may be affected by many genes that have not yet been identified; twin studies have shown that the AGA condition is heritable, and a family history of AGA has been included in our analysis for this reason. However, there are still many findings [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88] that suggest that heritable and epigenetic [69], [89] differences also play a role in alopecia; this may replace the classical discussion of the roles of genetic and environmental factors in alopecia.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional nature of the measurements of blood metals and personal behaviors (for example, sleep patterns [67], [68], [70], [94] and oily scalp [62], [95], [96], [97], [98], [99], [100]) limit our ability to identify causal relationships; the time of onset of moderate to severe hair loss will need more investigation in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data are limited, hair loss has also been associated with stressful conditions in both human and non‐human primates. For example, hairline recession and thinning in women was associated with having experienced a higher severity of stress and number of lifetime stressors . Similarly, patients with alopecia areata (AA), a dermatological condition that is associated with the sudden loss of hair from discrete areas, experienced a greater number of stressful life events, such as the loss of a family member, than did those without AA .…”
Section: Introductionmentioning
confidence: 99%
“…Gatherwright et al [68] compared 98 monozygotic female twins to identify possible environmental factors that may contribute toward AGA. Gatherwright et al [68] compared 98 monozygotic female twins to identify possible environmental factors that may contribute toward AGA.…”
Section: Associations and Comorbiditiesmentioning
confidence: 99%